“Keenly aware of environmental issues, yet wavering in conviction”: Understanding the factors influencing the consumers' willingness to pay for green energy - Ankita Sharma; Kishore Kumar; Rishi Dwesar (Sustainable Futures)
This paper aims to develop a framework to understand factors influencing millennial consumers’ intention and their willingness to pay (WTP) for green energy (GE) by extending the theory of planned behaviour (TPB). The study incorporates three additional constructs: belief about the cost of GE, concern for the environment, and green human capital (GHC) to the existing TBP model. Quantitative methodology was used to collect survey data from 517 millennials. The data was analysed using partial least square-structural equation modeling (PLS-SEM). Environmental attitude (EA), environmental subjective norms (ESN), GHC, belief about the cost of GE, and environmental concern were found to have a positive relationship with the consumer's intention to use GE and their WTP for GE. Results show that perceived behavioural control (PBC) had an insignificant influence on millennial consumers’ intention to use GE. This study makes practical and theoretical contributions by providing insights into the drivers of GE consumption intentions of millennial consumers. This research also contributes to the sustainable development policy literature by suggesting directions for future policy development, taking into consideration India's unique characteristics. This is one of the first studies to develop a framework to understand factors influencing millennial consumers’ intention and their willingness to pay (WTP) for green energy products in the context of an emerging economy like India.